Functional BDNF rs7124442 Variant Regulated by miR-922 is Associated with Better Short-Term Recovery of Ischemic Stroke - Liu B; He W; Liu D (Dove Medical Press, 2019)
Binghui Liu,1,* Wei He,1,2,* Dinghua Liu2,3 1Department of Neurology, The First People’s Hospital of Huocheng, Yili, People’s Republic of China; 2Department of Neurology, The Affiliated Jiangyin People’s Hospital of Southeast University Medical College, Wuxi, People’s Republic of China; 3Department of Physical Medicine and Rehabilitation, The Affiliated Jiangyin People’s Hospital of Southeast University Medical College, Wuxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dinghua LiuDepartment of Neurology, The Affiliated Jiangyin People’s Hospital of Southeast University Medical College Southeast University Medical College, Shoushan Road 163, Jiangyin, Wuxi 214400, People’s Republic of ChinaTel +86-159 9535 2188Email liudinghuacn@163.comBackground: Brain-derived neurotrophic factor (BDNF) is the most abundant neurotrophin, which contributes to the neuronal survival and synaptic plasticity. This study investigated the associations of BDNF polymorphisms at the 3ʹ-untranslated region with risk and outcome of ischemic stroke in a Chinese Han population.Methods: 500 patients and 520 controls were enrolled for BDNF rs7124442 genotyping. The binding of miR-922 to BDNF rs7124442 was examined by luciferase assay; BDNF expression was assessed using qRT-PCR.Results: Alcohol consumption, cigarette smoking, diabetes, hypertension (all P < 0.001) and higher serum triglycerides concentration (P = 0.009) were associated with an increased risk of developing ischemic stroke. After adjusted for age and sex, logistic regression analysis showed that IS patients harbored with rs7124442 TC genotype had a milder initial stroke (Dominant model: OR = 0.45, 95% CI = 0.25–0.81, P = 0.015), and also showed a better short-term recovery (Dominant model: OR = 0.39, 95% CI =0.24–0.68, P = 0.003). Furthermore, we found that co-transfection of hsa-miR-922 mimics with BDNF 3ʹ-UTR containing the mutated allele C changed luciferase activity when compared to co-transfection with BDNF 3ʹ-UTR containing the wild-type allele. Besides, patients carrying BDNF rs712444 TC or CC genotype had an increased level of BDNF compared with patients with the TT genotype.Conclusion: Our study demonstrates that the SNP rs7124442 in BDNF 3ʹ-UTR, through affecting the regulatory role of miR-922 in BDNF expression, might act as a protective factor for the outcome of patients with ischemic stroke.Keywords: ischemic stroke, polymorphism, brain-derived neurotrophic factor, BDNF, miR-922, outcome